Developing Industry Competences in Higher Education as a Factor in Ensuring Safety of Nuclear Industry Enterprises - M. V. Golovko; A. A. Lapkis; A. N. Setrakov (Глобальная ядерная безопасность, 2022)
The article justifies the importance of applying the competency-based approach for personnel training in accordance with the current demands of the real economy sector. An example of the development and implementation of the system approach by enterprises of the State Atomic Energy Corporation "Rosatom" to form the competence "Technological systems of power facilities" is given. The importance of this competence of ensuring the growth of productivity, efficiency and safety of nuclear power plants (NPPs) operation was noted. Involvement of educational organizations, enterprises of nuclear industry and other interested parties allows to approach comprehensively to the solution of an actual problem of development of in-demand skills and abilities of future specialists. The essence features of the competence are considered, as well as the plan and measures for its popularization both within enterprises and educational organizations in the territory of NPP presence.